1995
DOI: 10.1007/bf00127270
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of three fluorescent derivatives of gastrin

Abstract: As a first step in the study of hormone interaction with gastrin receptor-expressing cells, three fluorescent derivatives of heptagastrin were synthesized, characterized and tested for specificity and affinity towards gastrin/ CCKB receptor by means of confocal laser scanning microscopy (CLSM). Cyanine dye Cy3.29 and borfluoropyrromethene (BODIPY) derivatives of the hormone were found to be absorbed into the cells and concentrated in perinuclear organelles by a non-receptor mediated process. The BODIPY derivat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…In a previous study we compared the properties of three fluorescent derivatives of gastrin, rhodamine green, BODIPY, and Cy3.29 heptagastrin (25). The rhodamine green (RG) moiety provided the strongest fluorescence intensity, chemical and light stability and resistance to intracellular degradation within the cells necessary for the kinetic studies of ligand uptake.…”
Section: Fluorescent Derivatives Of Cck-8mentioning
confidence: 99%
See 1 more Smart Citation
“…In a previous study we compared the properties of three fluorescent derivatives of gastrin, rhodamine green, BODIPY, and Cy3.29 heptagastrin (25). The rhodamine green (RG) moiety provided the strongest fluorescence intensity, chemical and light stability and resistance to intracellular degradation within the cells necessary for the kinetic studies of ligand uptake.…”
Section: Fluorescent Derivatives Of Cck-8mentioning
confidence: 99%
“…Cy3.29 derivatives have emission maximum at 570 nm and do not emit below 540 nm and thus allow for simultaneous detection of the GFP fluorescence. Rhodamine green and Cy3.29-CCK-8 were obtained by the method used earlier for the synthesis of heptagastrin derivatives (25). The structures of the compounds were confirmed by NMR and mass spectroscopy.…”
Section: Fluorescent Derivatives Of Cck-8mentioning
confidence: 99%
“…The mechanisms of endocytosis of GRCP were studied for a small number of receptors (Ghinea et al 1992;Hoxie et al 1993;Ashworth et al 1995;Grady et al 1995;Roettger et al 1995) but the data are incomplete and controversial. We have previously described the synthesis and characterization of three fluorescent derivatives of heptagastrin (Czerwinski et al 1995). One of the derivatives, rhodamine green heptagastrin (RG-7G), was found to interact specifically with the gastrin/CCK-B receptor while retaining the biological properties of the parent peptide.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated that K d for the fluorescent gastrin derivatives was in the nanomolar range (e.g., 2 nM for rhodamine green-7G conjugate; ref. 28). Therefore, we would predict that the resultant cytotoxic effect of a drug conjugated with a peptide ligand would become apparent only close to the concentration defined by K d .…”
Section: Fig 2 Confocal Laser Scanning Microscopy Image Of Cckbr Nimentioning
confidence: 97%
“…Subsequent studies in our laboratory, which used fluorescent-labeled heptagastrin and CCK-8 (11,28,29), showed that both CCKBR and CCK-A receptor agonists undergo internalization by endocytosis upon binding to the receptors. The receptors and ligands are sorted in endosomes (11).…”
Section: More Toxic To Cholecystokinin Type B Receptor-positive Nih͞ mentioning
confidence: 99%